The impact of precession on the observed population of ULXs. Issue 2 (23rd October 2021) - Khan, Norman; Middleton, Matthew J; Wiktorowicz, Grzegorz; Dauser, Thomas; Roberts, Timothy P; Wilms, Joern
ABSTRACT: The discovery of neutron stars (NSs) powering several ultraluminous X-ray sources (ULXs) raises important questions about the nature of the underlying population. In this paper, we build on previous work studying simulated populations by incorporating a model where the emission originates from a precessing, geometrically beamed wind-cone, created by a supercritical inflow. We obtain estimates – independent of the prescription for the precession period of the wind – for the relative number of ULXs that are potentially visible (persistent or transient) for a range of underlying factors such as the relative abundance of black holes or NSs within the population, maximum precessional angle, and low-mass X-ray binary duty cycle. We make initial comparisons to existing data using a catalogue compiled from XMM–Newton . Finally, based on estimates for the precession period, we determine how the eROSITA all-sky survey ( eRASS ) will be able to constrain the underlying demographic.